Dampak Dukungan Pimpinan, Dukungan Rekan Kerja, dan Dukungan Keluarga terhdap Motivasi Kerja Pegawai Bank Panin - Harras, Hadyati (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study focuses on the importance of support from various sources in motivating employees. Support from supervisors, colleagues, and family is considered a key factor influencing employee motivation, particularly in the banking sector. The aim of this research is to analyze the impact of supervisor support, colleague support, and family support on employee motivation at PT Bank Panin. The research employs a quantitative method with multiple linear regression analysis to evaluate the relationships between these variables. The study subjects consist of 85 employees from PT Bank Panin, selected through simple random sampling. Data were collected via a questionnaire and analyzed using validity tests, classical assumption tests, and hypothesis testing to ensure the accuracy and validity of the results. The findings indicate that supervisor support and colleague support have a significant positive impact on employee motivation, while family support also contributes but to a lesser extent. This research provides valuable insights for management in designing strategies to enhance employee motivation through various forms of support.